2004
DOI: 10.1126/science.1095932
|View full text |Cite
|
Sign up to set email alerts
|

Post-Perovskite Phase Transition in MgSiO 3

Abstract: In situ x-ray diffraction measurements of MgSiO 3 were performed at high pressure and temperature similar to the conditions at Earth's core-mantle boundary. Results demonstrate that MgSiO 3 perovskite transforms to a new high-pressure form with stacked SiO 6 -octahedral sheet structure above 125 gigapascals and 2500 kelvin (2700-kilometer depth near the base of the mantle) with an increase in density of 1.0 to 1.2%. The origin of the D″ se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
731
2
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,254 publications
(774 citation statements)
references
References 26 publications
35
731
2
6
Order By: Relevance
“…Due to its large uncertainties, the phase change from perovskite to post-perovskite was not investigated in this study. This transition may, however, occur in Earth's lowermost mantle just above CMB (Murakami et al 2004;Oganov & Ono 2004). Previous numerical studies suggested that this phase change may have important implications in terms of dynamics and evolution of the Earth's mantle (e.g.…”
Section: O N C L U D I N G Discussionmentioning
confidence: 96%
“…Due to its large uncertainties, the phase change from perovskite to post-perovskite was not investigated in this study. This transition may, however, occur in Earth's lowermost mantle just above CMB (Murakami et al 2004;Oganov & Ono 2004). Previous numerical studies suggested that this phase change may have important implications in terms of dynamics and evolution of the Earth's mantle (e.g.…”
Section: O N C L U D I N G Discussionmentioning
confidence: 96%
“…Recent developments in mineral physics, which are not accounted for in this study, may complicate the interpretation of seismic information, and modify our inferences. Murakami et al (2004) reported a new phase transition from perovskite to post-perovskite around 2700 km. We did preliminary tests using available thermo-elastic data for postperovskite (Tsuchiya et al, 2004a,b), but we did not find any dramatic differences compared to the sensitivities plotted in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Even for MnSiO 3 the mixture of MnO + SiO 2 may be favored compared to perovskite because Mn 2+ with five 3d electrons at the octahedral site also has a large volume reduction by the high spin -low spin transition. and CaIrO 3 , transform to the CaIrO 3 -type post-perovskite structure (Murakami et al, 2004;Oganov and Ono, 2004;Hirose and Fujita, 2005;Tateno et al, 2006). In this diagram, the compounds marked by solid symbols mean that their distortions increase with pressure, while the compounds marked by open symbols mean that their distortions decrease with pressure (Tateno et al, 2006).…”
Section: Stability Of the Perovskite Structure In Fesio 3 Mnsio 3 Amentioning
confidence: 99%